Enhancing the expression of a key mitochondrial enzyme at the inception of ischemia-reperfusion injury can boost recovery and halt the progression of acute kidney injury - Corridon, Peter R. (Frontiers in Physiology, 2023)
Hydrodynamic fluid delivery has shown promise in influencing renal function in disease models. This technique provided pre-conditioned protection in acute injury models by upregulating the mitochondrial adaptation, while hydrodynamic injections of saline alone have improved microvascular perfusion. Accordingly, hydrodynamic mitochondrial gene delivery was applied to investigate the ability to halt progressive or persistent renal function impairment following episodes of ischemia-reperfusion injuries known to induce acute kidney injury (AKI). The rate of transgene expression was approximately 33% and 30% in rats with prerenal AKI that received treatments 1 (T1hr) and 24 (T24hr) hours after the injury was established, respectively. The resulting mitochondrial adaptation via exogenous IDH2 (isocitrate dehydrogenase 2 (NADP+) and mitochondrial) significantly blunted the effects of injury within 24 hours of administration: decreased serum creatinine ( 60%, p < 0.05 at T1hr;  50%, p < 0.05 at T24hr) and blood urea nitrogen (50%, p < 0.05 at T1hr;  35%, p < 0.05 at T24hr) levels, and increased urine output ( 40%, p < 0.05 at T1hr;  26%, p < 0.05 at T24hr) despite elevated histology injury score (26%, p < 0.05 at T1hr; 47%, p < 0.05 at T24hr). Therefore, this study identifies an approach that boosts recovery and halts the progression of AKI at its inception.